Regulation of cilium length and intraflagellar transport by the RCK-kinases ICK and MOK in renal epithelial cells. - Joost R Broekhuis (PLoS ONE, 2014)
Primary cilia are important sensory organelles. They exist in a wide variety of lengths, which could reflect different cell-specific functions. How cilium length is regulated is unclear, but it probably involves intraflagellar transport (IFT), which transports protein complexes along the ciliary axoneme. Studies in various organisms have identified the small, conserved family of ros-cross hybridizing kinases (RCK) as regulators of cilium length. Here we show that Intestinal Cell Kinase (ICK) and MAPK/MAK/MRK overlapping kinase (MOK), two members of this family, localize to cilia of mouse renal epithelial (IMCD-3) cells and negatively regulate cilium length. To analyze the effects of ICK and MOK on the IFT machinery, we set up live imaging of five fluorescently tagged IFT proteins: KIF3B, a subunit of kinesin-II, the main anterograde IFT motor, complex A protein IFT43, complex B protein IFT20, BBSome protein BBS8 and homodimeric kinesin KIF17, whose function in mammalian cilia is unclear. Interestingly, all five proteins moved at ∼0.45 µm/s in anterograde and retrograde direction, suggesting they are all transported by the same machinery. Moreover, GFP tagged ICK and MOK moved at similar velocities as the IFT proteins, suggesting they are part of, or transported by the IFT machinery. Indeed, loss- or gain-of-function of ICK affected IFT speeds: knockdown increased anterograde velocities, whereas overexpression reduced retrograde speed. In contrast, MOK knockdown or overexpression did not affect IFT speeds. Finally, we found that the effects of ICK or MOK knockdown on cilium length and IFT are suppressed by rapamycin treatment, suggesting that these effects require the mTORC1 pathway. Our results confirm the importance of RCK kinases as regulators of cilium length and IFT. However, whereas some of our results suggest a direct correlation between cilium length and IFT speed, other results indicate that cilium length can be modulated independent of IFT speed.